2017
DOI: 10.1016/j.bbmt.2016.11.005
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors and Outcomes of Infections by Multidrug-Resistant Gram-Negative Bacteria in Patients Undergoing Hematopoietic Stem Cell Transplantation

Abstract: The objective of this study was to determine risk factors and outcomes of infections by multidrug-resistant gram-negative (MDR GN) bacteria in 241 recipients of hematopoietic stem cell transplantation (HSCT). The cumulative incidence of infections was 10.5% (95% CI, 12.0% to 25.8%), with 57% of infections occurring during the period of severe neutropenia (neutrophil count < .1 × 10/L). In multivariate analysis, allogeneic transplant and colonization with MDR GN bacteria at admission to the transplant unit were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 25 publications
5
27
4
Order By: Relevance
“…As previously described, BSI after HSCT is associated with increased mortality [25]. The poor outcomes in patients with BSI may be multifactorial, including prolonged and profound neutropenia, the disruption of protective barriers such as mucosal surfaces and skin, and more severe immunosuppression [25][26][27]. In the present study the survival outcomes (OS and FFS) of patients with BSI before transplantation were poorer than those of patients without BSI.…”
Section: Discussionsupporting
confidence: 51%
“…As previously described, BSI after HSCT is associated with increased mortality [25]. The poor outcomes in patients with BSI may be multifactorial, including prolonged and profound neutropenia, the disruption of protective barriers such as mucosal surfaces and skin, and more severe immunosuppression [25][26][27]. In the present study the survival outcomes (OS and FFS) of patients with BSI before transplantation were poorer than those of patients without BSI.…”
Section: Discussionsupporting
confidence: 51%
“…Several studies reported risk factors for cephalosporin-resistant, ESBL-pro or MDR bacteria in cancer and HSCT patients [10,12,13,16,22,29,32]. Onl handful describe risk factors for carbapenem-resistant infections in popula involving but not limited to transplant patients, mainly for K. pneumoniae.…”
Section: Outcomementioning
confidence: 99%
“…In a recent large prospective Italian multicenter study performed on behalf of Gruppo Italiano Trapianto Midollo Osseo in the HSCT population, the overall survival (OS) at 4 months in patients developing pre-engraftment Pseudomonas aeruginosa and carbapenem-resistant (CR) Klebsiella pneumoniae (CR-Kp) bloodstream infectious (BSI) episodes was 25% and 40%, respectively, with pretransplant carriers having a probability of approximately 30% of development a subsequent colonizing pathogen-related infection [12]. According to some recent studies, patients developing an MDR-GNB infection after allo-HSCT have a poor outcome, so that their eligibility to allogeneic procedure is generally carefully evaluated for the risk-to-benefit ratio [13].…”
Section: Introductionmentioning
confidence: 99%